Catabolism of [1-(14)C]Levulinic Acid by Etiolated and Greening Barley Leaves - Duggan, Jeffrey X. (1981)
Levulinic acid (LA), a competitive inhibitor of δ-aminolevulinic acid (ALA) dehydratase (EC 4.2.1.24), has been used extensively in the study of ALA formation during greening. When [1-(14)C]LA is administered to etiolated barley (Hordeum vulgare L. var. Larker) shoots in darkness, (14)CO(2) is evolved. This process is accelerated when such tissues are incubated with 2 millimolar ALA or placed under continuous illumination. Label from the C-1 of LA becomes incorporated into organic acids, amino acids, sugars, lipids, and proteins during a 4-hour incubation in darkness or in the light. This metabolism is discussed in relation to the use of LA as a tool in the study of chlorophyll synthesis in higher plants.